CMS at 13: a retrospective of the journey. Issue 1 (8th March 2021) - Farrukh, Muhammad; Raza, Ali; Meng, Fanchen; Wu, Yihua
Abstract : Purpose: To commemorate the 13th anniversary of the Chinese Management Studies (CMS) and suggest future research directions, this study aims to present an overview of the CMS through a systematic bibliometric analysis from 2007 to 2019. The analysis emphasizes the trend of themes, structure of publications and citations, the most cited publications, the most productive authors, universities, countries and regions. Design/methodology/approach: The study uses the data extracted from the Scopus database to present an overview; besides, it also uses VOSviewer and Bibliometrix software packages to visualize the intellectual network of CMS. Findings: This analysis is based on 486 publications between 2007 and 2019. Results show that there is a rising trend in the number of citations to CMS. The researchers from China were the most frequent contributors to the journal, whereas researchers from the USA, Taiwan, Singapore and Australia were well represented. In addition, the results show that innovation, leadership, human resource management and corporate social responsibility have been the most important research themes in the journal. Practical implications: This study offers an objective view of the CMS publication structure. The study's findings can help the journal readers obtain a quick snapshot of the leading trends occurring in the journal. Furthermore, this study provides future research directions for the journals by underscoring important themes. Originality/value: As the journal's first retrospective, this study not only educates and enriches CMS' global readers and aspiring contributors but can also be useful to its editorial board, as it provides several inputs in the form of future research directions to guide the journal's progress.